Kritik Mimetik Pada Puisi “Brutus” Karya Fadli Zon - Ismail Shabri (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2024)
This article aims to analyze mimetic criticism in the poem "Brutus" by Fadli Zon. This research uses a qualitative method with a mimetic approach. Data collection was carried out through document review using techniques of reading, listening and recording relevant information. The aim of this research is to identify and explain the types of symbols and meanings contained in the poem Brutus by Fadli Zon. Based on the research results, 14 data symbols were found, namely 9 private symbols were found, while 5 blank symbols were recorded, and no natural symbols were found. In terms of meaning, 14 data were found, namely ideational meaning dominated with 8 findings, followed by emotive and referential meaning, with 3 findings each.